Introducing unadapted, insect-resistant maize germplasm in three-way hybrid combinations for resistance to the maize stalk borer, Buáeola fusca (Fuller) (Lepidoptera : Noctuidae) - Van Rensburg, J.B.J.
Sumario (En)
Ilus.; 10 ref.
Keywords: ZEA MAYS; GERMOPLASMA; HIBRIDOS; BUáEOLA FUSCA; LEPIDOPTERA; RESISTENCIA A LAS PLAGAS; CONTROL QUIMICO